Association of the systemic immune-inflammation index (SII) and clinical outcomes in patients with stroke: A systematic review and meta-analysis - Huang, Yong-Wei; Yin, Xiao-Shuang; Li, Zong-Ping (Frontiers in Immunology, 2022)
OBJECTIVE: A novel index called systemic immune-inflammation index (SII), has been proved to be associated with outcomes in patients with cancer. Although some studies have shown that the SII is a potential and useful tool to diagnosis and predict the advise outcomes in stroke patients. Nevertheless, the findings is controversial, and its association with clinical outcomes is not clear. Consequently, we performed a systematic review and meta-analysis to investigate the association of SII and clinical outcomes in patients with stroke. METHODS: A search of the PubMed, Embase, Cochrane Library, Scopus, and Web of Science was conducted. Our study complied with the PRISMA (the Preferred Reporting Items for Systematic Reviews and Meta-Analyses) strictly. We used the NOS (Newcastle-Ottawa Scale) tool to assess the potential bias of included studies. The end points including poor outcome, mortality, severity of stroke, hemorrhagic transformation (HT) were statistically analyzed. RESULTS: Seventeen retrospective studies met the eligibility criteria, and a total of 18161 stroke patients were included. Our study showed that high SII is significantly associated with poor outcome, high mortality, and the incidence of HT . Besides, we also investigated the difference of SII in poor/good outcome, death/survival, and severity of stroke. Our analysis demonstrated that the SII of poor outcome, death, and moderate-to severe stroke group was much higher than that of good outcome, survival, and minor stroke group, respectively. However, no significant influence was observed of SII for recanalization. CONCLUSIONS: To our best knowledge, this may be the first meta-analysis assessing the relationship of SII and clinical outcomes of stroke patients. Inflammatory response after stroke is valuable for applications in immunoregulatory therapy. Stroke patients with elevated SII should be closely monitored, which may be a potential therapeutic strategy to limit brain damage following stroke. Thus, study of SII and clinical outcomes of stroke patients is critical. Our preliminary findings could reflect the actual situation in the clinic and assist clinical decision-makers. Nevertheless, further studies are needed for dynamic monitoring of SII to better understand the value of SII. Massive-sample and multi-center studies are needed to obtain more robust results.